Diskursus Pendidikan Karakter di Perguruan Tinggi dalam Pandemi Covid-19 - Fatimah Zuhra; Usfur Ridha (Jurnal Riset dan Pengabdian Masyarakat, 2021)
This study examines the importance of character education in students of Indonesia during the Covid-19 pandemic, especially those who are currently undergoing the online learning process. The character of education is really needed not only in school or college but also at home and in the social environment itself. Furthermore, students in colleges are no longer monitored by their parents during the learning process so that character or manners while studying are no longer something that must be observed and considered important in distance learning. This study is a literature study sourced from library materials using a qualitative approach. Thus, the research activity is the exploration of a number of data both primary and secondary with some concrete steps such as reading and studying primary data in the form of research books, theses or dissertations related to character education and its relationship with Pandemic Covid-19. Character education for students is needed because so far students are only preoccupied with lecture materials in the classroom, but pay less attention to the meaning and value behind the process itself. The situation becomes more difficult when classroom learning turns into distance learning and students cannot be fully monitored by lecturers and less participation from parents who pay less attention to character education at home.